Knowledge Management and Developing Human Resources in the Secretariat of the Central Library- Baghdad University (Journal of the College of Education for Women, 2019)
Knowledge management contribute to the overall private university libraries to develop libraries for the purpose of creating human and technological resources by investing research and development, as well as education and training for life.This study followed the methodology of the descriptive and historical pillars of knowledge management for the years 1990 to the present day in 2017, depending on statistical figures obtained by the researchers from the General Secretariat of the Central Library at the University of Baghdad, and the Human Resources Division, which specialized human resources training after 2004 (and before those years from 1982 until 2002, where the continuing education was committee of the fixed committees are working in cooperation with the Electronic and Computer Center at the University of Baghdad, and the training was for landlords it will be according to the library need of technical development or at the request of the employee)Using modern technology and techniques for the purpose of technically and administratively rehabilitation, comparing this phase with the previous stages to find out the results of the comparison and the statement of the importance of training and education, and how to address